Metabolic syndrome diagnosis and widespread high grade prostatic intraepithelial neoplasia significantly increase prostate cancer risk: results from a multicenter biopsy study. Issue 1 (December 2016) - Cicione, Antonio; De Nunzio, Cosimo; Tubaro, Andrea; Cantiello, Francesco; Manno, Stefano; Oliveira, Carlos; Lima, Estevao; Damiano, Rocco
Abstract Background To test in multicenter setting if patients affected of metabolic syndrome (MetS) and initial widespread high grade prostatic intraepithelial neoplasia (wHGPIN) diagnosis are at higher risk of prostate cancer (PCa) on repeat biopsy. Methods Patients clinical charts from three European Academic Hospital were reviewed in order to identify patients with initial diagnosis of HGPIN undergone to repeat biopsy. Inclusion and exclusion criteria were adopted to minimize patient heterogeneity. MetS was defined according to Word Heart Organization criteria while initial wHGPIN when ≥4 cores biopsy were involved. A multivariate logistic model was computed to assess the association between PCa and clinical-pathological variables. Results Overall 283 patients were scheduled. Median age was 67 years (IQR 62–72). MetS was diagnosed in 116/283 (41 %) patients and PCa was detected in 84/283 (29.7 %) patients. In particular, PCa was more frequently diagnosed in patients affected of wHGPIN and MetS (45/86, 52.3 %) than in patients with wHGPIN and normal metabolic profile (28/95, 29.5 %), p = 0.002. The multivariate logistic model confirmed that wHGPIN and MetS are independent risk factors for following PCa diagnosis, respectively OR 2.4 (95 % CI 1.01–5.71, p = 0.04), OR 2.79 (95 % CI 1.49–5.22, p = 0.01) while total PSA and DRE findings are not able to predict PCa at repeat biopsy, OR 1.05 (95 % CI 0.98–1.03p = 0.69) and OR 1.01 (95 % CI 0.55–1.84, p = 0.96) respectively. Conclusions wHGPIN is positively associated to PCa; assessing metabolic profile and repeat prostate biopsy is advisable in patients with initial diagnosis of wHGPIN.